The Spiritual Health Services in the Face of the COVID-19 Pandemic: A Hybrid Study - Asadzandi Minoo; Abolghasemi Hasan (Journal of Patient Care and Services, 2021)
Background COVID-19 as an infectious disease, and deadly biological crisis, threatens the bio-psycho-social- spiritual health of the people. Spiritual health from the perspective of Islam, means having a sound heart, living in the present time with sense of peace, security, patience and gratitude, safe from the fear and anxiety of future, grief and regret for the past events. It affects other dimension of health. This study was conducted to investigate the spiritual health services in the face of the COVID-19 pandemic in a Muslim society. Methods This qualitative study was conducted from March 1, 2020 to the end of May 2020 in Tehran by using the Schwartz and Kim's hybrid model concept analysis with a deductive / inductive analysis approach, in three stages: 1- Theoretical review of religious and scientific evidence, 2- Field research 3- Final analysis. Data collection was done in hospitals and hospices by semi-structured interviews, taking notes, websites and social networks search. Data were analyzed by
Keywords: COVID-19